Improvement To Shunt Contactors For External Floating Roof Tank Lightning Protection System - Mohd Yusri B. Mohd Yusoff, Mohd Yusri (Universiti Teknologi Petronas, 2010)
This project is an improvement to the current FRT's lightning protection system to prevent the formation of electrical spark during a lightning strike; this is one of the main causes of rim fire on an external floating roof tank. During internship at PETRONAS Penapisan Terengganu Sdn. Bhd. (PPTSB), the engineers are trying to prevent more fire incident from occurring on their floating roof tank that are used to store highly volatile petroleum products.